The Relationship Between Social Media Engagement and BodyEsteem Among Undergraduates From International Islamic University - Nada Nael, Hirzalla; Siti Hasanah, Azahari; Zubiya, Siddiqui (Universitas Muhammadiyah Yogyakarta, 2021)
Introduction – As the use of social media continues to increase, past research has linked its use with various emotional and physical problems, such as body image distortion and eating disorders. University students have been found to be particularly susceptible to having poor body image. Purpose – This prompted the present study to examine the relationship between social media engagement and body[1]esteem among students in a public Malaysian university. Methodology/Approach – This study hypothesised that social media engagement is significantly associated with body-esteem. By adopting a correlational study, this research involved undergraduate students (N=116) from International Islamic University Malaysia (IIUM) who were required to fill in the Social Media Engagement Questionnaire (SMEQ) and Body-Esteem Scale Revised (BES-R) through an online survey. A Spearman’s correlation analysis was used to identify the correlation between social media engagement (M=22.46, SD=8.06) and body-esteem (M=93.39, SD=19.33). Findings – Results found that there was a significant yet weak positive relationship between the two variables examined (p = 0.05, 2 tailed), indicating that higher social media engagement is correlated with higher body-esteem. Originality/ Value/ Implication – These findings imply that social media engagement does not necessarily facilitate negative outcomes such as low body esteem as suggested by past studies. Instead, interactions through social media can aid in increasing body esteem. Nonetheless, as revealed by past research, this positive outcome may depend on the content that social media users engage with